Arte do espaço, espaço da arte: fronteiras da land art (1967-1977) - Guimarães, Ana Lúcia (2019)
This work discusses characteristics of the relationship that develops during the 1960s and 1970s between art, specifically the proposals of land art, space and nature. We take as a starting point the perception of the categories art and nature as cultural constructions of a given time and space. The context of the 1960s, marked by post-World War II economic, political, and geographical upheavals, the new Cold War nuclear threats, the technological invasion of daily life, the explosion of women's rights, black, student, environment, from the growing criticism of institutions, is conducive for art to take new formal and conceptual directions. In this context, our goal is to conceptualize and contextualize the development and characteristics of land art from 1967 to 1977 and the attitude adopted by contemporary art in relation to its surroundings. To this end, we built a literature review based on the position of historians, philosophers, sociologists, art critics and artists, presenting artistic proposals that reiterate in an exemplary way our discussions. From this review, it is clear that land art artists explore the interconnection of art with other fields and / or concepts. Having the impetus to rethink the relationship between art and the environment, especially with space (in its historical, cultural and physical character), through the reinvention of the sculptural act inserted in it, the artists make use of large terrain, often removed from human intervention. Art seeks in nature no longer a mold to be represented and perfected by technique, but an interactive setting for its provocations, which become much more intellectual, leaving aside the centrality of object, vision and materiality in art. In their negation of the object and its materiality, they present to the public and the world the art, records of the existence of an artistic act / process, occurring in a time or space other than those of its exhibition. Photography increasingly assumes the expository physical place of the work of art, calling into question what is or is not considered art, expanding the boundaries of this concept. In addition to this technical questioning, through our investigations, we realize that earth art is an invitation to appreciate nature and the perception of space as part of human relations. Our research, in turn, invites us to understand these artistic practices as part of the socially constructed cultural world.